Problem-Solving Ability in terms of Adversity Quotient On SFE Learning Based on Firing Line - Limay Trisno Putra, Ari; Dwidayati, Nur Karomah; Isnarto, Isnarto (Universitas Negeri Semarang, 2020)
This study aims to determine the effectiveness of Student Facilitator and Explaining (SFE) learning based on Firing Line and mathematical problem-solving abilities in terms of Adversity Quotient (AQ). The method used is a mixed method with a sequential explanatory design. The study was conducted on class VIII of SMP Teuku Umar Semarang in the academic year 2018/2019 with class VIII 2 as the experimental class and class VIII 3 as the control class. Quantitative data collection with a problem-solving ability test and qualitative data collection is done by interview, observation, questionnaire, and documentation. The results of the problem-solving ability test were analyzed to determine the effectiveness of mathematics learning with the average completeness test, classical completeness test, proportional t-test, average t-test, and improvement test. Students are grouped according to the AQ category which consists of Quitters, Campers, and Climbers to then select three subjects from each category to be interviewed. The results of the study were obtained (1) effective SFE based on Firing Line learning; (2) mathematical problem-solving skills, Quitters students are able to understand problems and plan problem-solving. Campers students are able to understand problems, plan problem-solving and implement solutions. Student Climbers are able to understand problems, plan problem-solving, implement solutions, and re-examine the results of resolution.